1995
DOI: 10.1128/aem.61.12.4141-4146.1995
|View full text |Cite
|
Sign up to set email alerts
|

A direct PCR detection method for Clostridium tyrobutyricum spores in up to 100 milliliters of raw milk

Abstract: A direct detection method for Clostridium tyrobutyricum spores in up to 100 ml of raw milk is presented. The bacterial spores are concentrated by centrifugation after chemical extraction of the milk components. The vegetative cells are selectively lysed, and their DNA is digested and washed away. Afterwards, the DNA is liberated from the spores by microwave treatment. For the identification of the C. tyrobutyricum DNA, a two-step PCR method with two nested pairs of primers is used. The primers were derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…The specificity of Ct1F and Ct1R primer sets used in this study to C. tyrobutyricum is confirmed by Herman et al(1995) using 13 species of Clostridium. However, recently Kobayashi et al (2017) proposed a novel species C. pabulibutyricum which is closely related to C. tyrobutyricum.…”
Section: Specific Identification Of C Tyrobutyricum By Pcr Analysismentioning
confidence: 57%
See 1 more Smart Citation
“…The specificity of Ct1F and Ct1R primer sets used in this study to C. tyrobutyricum is confirmed by Herman et al(1995) using 13 species of Clostridium. However, recently Kobayashi et al (2017) proposed a novel species C. pabulibutyricum which is closely related to C. tyrobutyricum.…”
Section: Specific Identification Of C Tyrobutyricum By Pcr Analysismentioning
confidence: 57%
“…The main cause of late blowing is C. tyrobutyricum, and its detection rate is particularly important in cheese production (Klijn, Nieuwenhof, Hoolwerf, van der Waals, & Weerkamp, 1995;Sheehan, 2011). C. tyrobutyricum was identified by species-specific PCR by Herman, Block, and Waes(1995). The cells were harvested and resuspended in sterile water and centrifuged at 9,500× g for 1 min, then DNA was extracted by InstaGene matrix (Bio-Rad, Hercules, CA), then used as a template DNA.…”
Section: Specific Identification Of C Tyrobutyricum By Pcr Analysismentioning
confidence: 99%
“…Aside from the MPN method, only a few alternatives are available. A highly specific PCR method detects low numbers of C. tyrobutyn'curn; however, quantification based on that technology is not possible (Herman et al 1995;Kiljn ef al. 1995).…”
Section: Introductionmentioning
confidence: 99%
“…One consistent factor in these previous studies has been the use of an anaerobic environment for growth of C. tyrobutyricum. Though recent research has focused on using polymerase chain reaction technology to identify this microorganism, it is still not commonly used for quality testing within cheese processing plants (Herman et al 1995;Klijn et al 1995). Ali and Fung (1991) reported that the Fung Double Tube (FDT) method, which utilizes a small tube inserted into a larger tube with selective agar, could be used to enumerate C. perfringens in ground beef.…”
Section: Introductionmentioning
confidence: 99%